Problems of drug abuse in Commonwealth Caribbean countries - Pollard, Duke (CARICOM Secretariat GEORGETOWNGY, 1987)
Briefly reviews history of drug abuse and shows how weak economic conditions in the Caribbean foster its growth. Identifies the drugs that are abused and estimates their availability in the Region. Discusses the prevalence of the problem and reviews the work of several groups and organizations in the areas of preventive education and public information programmes. Compares the objectives of the preventive education programmes of Jamaica and the Bahamas with those of the WHO. Outlines the material, information and training needs for a regional programme on drug abuse abatement and control, and the available national resources. Makes recommendations for regional drug control.